Atbrīvošana no atbildības par zaudējumiem starptautiskajos preču pirkuma-pārdevuma darījumos - Bērziņa, Madara (Latvijas Universitāte, 2007)
Darbā tiek pētīti gadījumi, kad puses var tikt atbrīvotas no atbildības par zaudējumiem starptautiskajos preču pirkuma – pārdevuma darījumos. Lielāko vērību pievēršot 1980.gada Apvienoto Nāciju Konvencijā par starptautisko preču pirkuma līgumiem noteiktajam regulējumam. Pirmajā nodaļā tiek apskatīts nepārvaramas varas un grūtību koncepciju saturs un nozīme starptautisko preču pirkuma – pārdevuma darījumos. Otrajā nodaļā tiek analizēta atbrīvošana no atbildības par zaudējumiem, ja saistību izpilde kļuvusi neiespējama neparedzama šķēršļa, kas atrodas ārpus puses kontroles, dēļ. Savukārt, trešajā nodaļā - atbrīvošana no atbildības par zaudējumiem, kad saistību izpilde kļuvusi neiespējama puses rīcības dēļ.

The thesis examines an issue of exemption from liability to pay damages in international sales transactions. In particular, in the United Nations Convention on Contracts for the International Sale of Goods (CISG). The thesis consists of three chapters. The first chapter addresses the two major legal concepts dealing with the problem of changed circumstances – force majeure and hardship. The second and third chapter sets out concrete provisions of CISG. First, it deals with the issue, when, under certain extraordinary circumstances, a party’s obligation to perform may be excused if an unforeseen and unavoidable impediment, beyond the non-performing party’s control, obstructed performance. Second – when failure to perform was due to the first party’s act or omission. The author considers the acceptability and practical application of each of the abovementioned excuses in light of the legal doctrine, by analyzing the pronouncements from the rulings of the different domestic courts as well as decisions of arbitration. CISG avoids reference to the existing concept, because it has developed system of its own. But in practice, references to different approaches of domestic legal systems can be detected and that is against the purpose of CISG. Therefore, common understanding of above mentioned excuses should have been found.
Exemption from Liability for Damages in International Transactions of Sale of Goods
Keywords: Tiesības